PERAN KANTOR IMIGRASI KELAS IA SAMARINDA DALAM PENGAWASAN DAN PENINDAKAN ORANG ASING BERDASARKAN UNDANG – UNDANG NOMOR 6 TAHUN 2011 - Dina Paramitha Hefni Putri, Yenny Meilyana dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
In the implementation of surveillance and enforcement of foreigners in the East Kalimantan Region, Samarinda's Class I Immigration Office experienced a few obstacles including the presence, activities of foreigners, and abuse of residence permits of foreigners in the Samarinda area.  The real weaknesses in the surveillance system do not lie solely on rules because the existing regulatory system is quite complete and clear, but lies in the limited number of officers possessed by the Class I Immigration Office A samarinda.  Based on the background above, the writer wants to choose the title "The Role of Class I A Samarinda Immigration Office in Supervision and Enforcement of Foreigners Based on Law Number 6 Year 2011".  In this study the authors use the empirical juridical method, based on the results of the author's research and the discussion that has been described then the following conclusions can be drawn.  Regarding foreigners' supervision, it is carried out in stages with regard to foreigners who enter or reside in Samarinda, so it is quite clearly specified and what provisions have been set by the Immigration Office.  Suggestions for conducting oversight to increase the number of officers in each district / city area to be more efficient in the future.